2016
DOI: 10.1080/07347332.2016.1263265
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Korean mothers of children with cancer: A Photovoice study

Abstract: Using Photovoice, a participatory action research methodology, we investigated Korean mothers' lives postdiagnosis of their child with cancer. Photovoice was used to understand the mothers' perceptions of how they have adapted to their children's illnesses. Five mothers of children with cancer participated in five sessions of the Photovoice project, during which they took and shared photographs and narratives about their experiences and joined weekly group discussions on their selected themes. The following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Overall, the current results were consistent with those reported in western research 6 and Asian studies. 17 Despite cultural differences in quality of life between Singaporean caregivers and those in western countries, 8 the broader constructs of emotional and interpersonal experiences among parents of children with cancer appear universal across cultures. 6 However, the processes by which parents go through these experiences may differ in terms of the way they perceive, react and cope with their child's cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the current results were consistent with those reported in western research 6 and Asian studies. 17 Despite cultural differences in quality of life between Singaporean caregivers and those in western countries, 8 the broader constructs of emotional and interpersonal experiences among parents of children with cancer appear universal across cultures. 6 However, the processes by which parents go through these experiences may differ in terms of the way they perceive, react and cope with their child's cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Following the cancer diagnosis, parents reported experiencing significant emotional distress. 6,11,[17][18][19][20] In the current study, parents reported disrupted sleep quality, especially in the initial period of diagnosis, trauma and ongoing distress from caring for their child with cancer. As the child progresses to survivorship, parents continue to report uncertainty around their child' s health status.…”
Section: Intra and Interpersonal Needs As Universal Experiencesmentioning
confidence: 99%
“…13 Later, these photographs are shared publicly in order to enhance understanding of the participants and inspire multilevel change within communities. Photovoice has been used successfully in child caregiving populations including caregivers of children with cancer 14 and asthma. 15,16 Caregivers have noted that time/scheduling difficulties and guilt leaving their care recipient hinder accessing psychosocial services.…”
Section: Photovoice and Social Mediamentioning
confidence: 99%
“…research areas to gather information on community strengths and challenges 37 . Originally used with Chinese village women 35 , Photovoice research ranges from understanding issues related to mental health38 , learning difficulties39 , and experiences of cancer survivors40 .…”
mentioning
confidence: 99%